2018
DOI: 10.3399/bjgp18x697073
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination uptake in an Irish obstetric cohort

Abstract: BackgroundInfluenza infection during pregnancy can lead to significant maternal morbidity. There are limited data on influenza vaccination uptake and determinants of uptake in Irish obstetric populations.AimThe objectives of this study were to determine: the uptake of influenza vaccination during pregnancy; the determinants of vaccination uptake; knowledge, attitudes and concerns of postnatal women surrounding vaccination during pregnancy; and the recommendations of healthcare workers. Pertussis vaccination up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Healthcare professional recommendation affects the decision to accept vaccination and several reports implied aspects of vaccination discussion may be lacking; 59% of participants of one study described inadequate information from the healthcare professional as a reason for non-uptake [ 10 , 20 ]. This is important as it has been reported that mothers’ lack of knowledge and engagement with antenatal vaccination campaigns also contributed to non-uptake [ 10 , 30 , 31 ]. The possibility of disparity in information has been alluded to, in another study, where despite information offered by healthcare workers, large numbers of women were unvaccinated [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Healthcare professional recommendation affects the decision to accept vaccination and several reports implied aspects of vaccination discussion may be lacking; 59% of participants of one study described inadequate information from the healthcare professional as a reason for non-uptake [ 10 , 20 ]. This is important as it has been reported that mothers’ lack of knowledge and engagement with antenatal vaccination campaigns also contributed to non-uptake [ 10 , 30 , 31 ]. The possibility of disparity in information has been alluded to, in another study, where despite information offered by healthcare workers, large numbers of women were unvaccinated [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the UK, there isn't consensus among midwives about vaccination during pregnancy with 69% in agreement with it [ 30 ], 76% of midwives feeling they should routinely advise about vaccines in pregnancy and only 25% feel adequately prepared for that role [ 30 ]. A potential explanation for this is limited knowledge of risks to the foetus in pregnancy amongst health professionals which may be attributed to training variation and self-directed knowledge update requirements among midwives and doctors [ 31 ]. An alternative explanation may be that the healthcare professional's views on vaccination may be an influence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations